High‐density grids for efficient data collection from multiple crystals. Issue 1 (1st January 2016) - Baxter, Elizabeth L.; Aguila, Laura; Alonso-Mori, Roberto; Barnes, Christopher O.; Bonagura, Christopher A.; Brehmer, Winnie; Brunger, Axel T.; Calero, Guillermo; Caradoc-Davies, Tom T.; Chatterjee, Ruchira; Degrado, William F.; Fraser, James S.; et al.
Abstract : A high‐density sample mount has been developed for efficient goniometer‐based sample delivery at synchrotron and XFEL sources. Abstract : Higher throughput methods to mount and collect data from multiple small and radiation‐sensitive crystals are important to support challenging structural investigations using microfocus synchrotron beamlines. Furthermore, efficient sample‐delivery methods are essential to carry out productive femtosecond crystallography experiments at X‐ray free‐electron laser (XFEL) sources such as the Linac Coherent Light Source (LCLS). To address these needs, a high‐density sample grid useful as a scaffold for both crystal growth and diffraction data collection has been developed and utilized for efficient goniometer‐based sample delivery at synchrotron and XFEL sources. A single grid contains 75 mounting ports and fits inside an SSRL cassette or uni‐puck storage container. The use of grids with an SSRL cassette expands the cassette capacity up to 7200 samples. Grids may also be covered with a polymer film or sleeve for efficient room‐temperature data collection from multiple samples. New automated routines have been incorporated into the Blu-Ice Blu‐Ice / DCSS DCSS experimental control system to support grids, including semi‐automated grid alignment, fully automated positioning of grid ports, rastering and automated data collection. Specialized tools have been developed to support crystallization experiments on grids, including a universal adaptor, which allows grids to be filled by commercial liquid‐handling robots, as well as incubation chambers, which support vapor‐diffusion and lipidic cubic phase crystallization experiments. Experiments in which crystals were loaded into grids or grown on grids using liquid‐handling robots and incubation chambers are described. Crystals were screened at LCLS‐XPP and SSRL BL12‐2 at room temperature and cryogenic temperatures.